PEMAKNAAN PERLUASAN OBJEK SENGKETA TATA USAHA NEGARA YANG MELIPUTI TINDAKAN FAKTUAL - Fellista Ersyta Aji; Laga Sugiarto (Universitas Muhammadiyah Gresik, 2018)
The government is a legal subject that has little or no role in the survival of society. In performing its duties to serve the community, not infrequently the government issued a State Administrative Decision which is intended for certain communities. With the government issuing this, certainly not forever it is in accordance with existing regulations. Sometimes, decisions issued by the government actually even give the impact on harm to ordinary people. Then, with the administrative court and Act No. 5 of 1986 on Peratun, at least there are facilities for the public to sue the government and ask to cancel the decision made by the government. Then in Year 2014 came the Law No. 30 of 2014 on Government Administration. In this Government Administration Act more or less supersedes the provisions contained in the Law of the Peratun. Especially in this Law which attracts attention is the expansion of object disputes. The object of the TUN dispute in this Act is different from its elements to the Law of the Peratun. One of these is a written stipulation that includes factual action. There is no explanation for the meaning of factual acts in this Administrative Administration Act. Therefore, further research is needed in this regard